On the solitonic structures for the fractional Schrodinger-Hirota equation - Badshah, Fazal; Tariq, Kalim U.; İnç, Mustafa; Zeeshan, Muhammad (Springer, 2024)
In this article, the fractional Schrodinger-Hirota equation which is a generalization of the standard Schrodinger equation which, in particular, explain how soliton transmission behaves on fiber optic systems in physics when data is transmitted over long distances with a wide bandwidth. A collection of comprehensive soliton structures are developed to study the behaviour of the governing model with the aid of some efficient explicit strategies namely the exp(-psi(zeta))-expansion method and the Sardar sub-equation method. By transforming the original equation into a system of ordinary differential equations, it becomes possible to obtain explicit solutions with a high degree of accuracy. These solutions incorporate dark soliton and trigonometric function solutions, dark singular solition plane wave, singular solition, opposite singular solition, smooth, bell shaped, w-shaped periodic, bright, anti kink, singular bell shaped solitons and traveling wave structures.
Keywords: The Schrodinger equation; Analytical solutions; Nonlinearity; Fractional derivatives; Nonlinear optics; The Sardar sub-equation method and the exp(-psi(zeta))-expansion method